IMPLEMENTATION OF THE FREE NUTRITIOUS MEAL PROGRAM: A SYSTEMATIC LITERATURE REVIEW - Muammar Rinaldi; Joni Gusmali Agus Selayan; Susanna Silvia Sembiring; Cecep Indra Surawijaya; Heryanto Hulu (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The Free Nutritious Meal Program (MBG) is a strategic initiative launched by the Indonesian government in January 2025 to accelerate stunting reduction and enhance human capital quality in support of the Indonesia Emas 2045 vision. This study aims to consolidate scientific evidence regarding MBG implementation through a Systematic Literature Review (SLR) following PRISMA 2020 guidelines. Literature searches conducted on the Scopus database yielded 11 articles that met the inclusion criteria for analysis. The findings demonstrate that the MBG program provides significant positive impacts across three main dimensions: health and nutrition (stunting prevention and food security), education (improved concentration, academic achievement, and attendance rates), and socio-economics (reduced household burdens and local economic empowerment through MSMEs). Program evaluation employs four indicator groups: health, education, governance, and socio-economic resilience. While substantial opportunities for long-term human resource development were identified, serious structural challenges remain, including logistical constraints in remote and underserved areas, infrastructure limitations, fiscal risks, and the need for governance transparency to prevent corruption. The success of MBG is highly dependent on the collaborative commitment of stakeholders in building an accountable and participatory governance system.